2016
DOI: 10.3390/ijerph13040363
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Green Outdoors versus Indoors Environmental Settings on Psychological and Social Outcomes of Controlled Exercise

Abstract: This study addressed a methodological gap by comparing psychological and social outcomes of exercise in green outdoors versus built indoors settings, whilst rigorously controlling exercise mode and intensity. The hypotheses were that greater improvements or more desirable values for directed attention, mood, perceived exertion, social interaction time, intention for future exercise behaviour and enjoyment would be associated with outdoors compared to indoors exercise. Following a baseline session, paired parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 69 publications
5
96
1
20
Order By: Relevance
“…16 There is a type of exercise called green, which is given to activity practiced in nature, with behavioral results in stress relief in acute exercise sessions. 17 Outdoor physical activity would be its accomplishment in squares, parks and field environments. 18 The most popular of these activities is walking, practiced by the elderly with the goal of improving health and preventing diseases.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…16 There is a type of exercise called green, which is given to activity practiced in nature, with behavioral results in stress relief in acute exercise sessions. 17 Outdoor physical activity would be its accomplishment in squares, parks and field environments. 18 The most popular of these activities is walking, practiced by the elderly with the goal of improving health and preventing diseases.…”
Section: Physical Activitymentioning
confidence: 99%
“…According to current knowledge, the skin is the only organ capable of producing vitamin D, which is also absorbed from dietary intake. 22 There is research indicating the practice of physical activity in outdoor settings, but they do not mention the importance of vitamin D. 17,23 Similarly, there are studies on the synthesis of vitamin D from the incidence of sun rays on the skin, but they do not mention physical activity with sun exposure. 24 Why not consider outdoor physical activity in view of the benefits of such activity along with the possibility of vitamin D synthesis from skin exposure to ultraviolet B?…”
Section: Physical Activitymentioning
confidence: 99%
“…Previous research has indicated that environmental factors may influence the rates of physical activity [10,11], and living close to urban parks or other green spaces is linked to increased levels of physical activity [12][13][14][15]. Research has also found that conducting exercise in a green environment is more beneficial than doing the same exercise in an indoor environment [16]. By visiting urban parks, diverse and significant health benefits can be obtained, such as better sleep, stronger muscles, improved mood, reduced stress, and social contact [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recreational runners were found to have higher scores on pride scale when running in the nature environment than running in the laboratory environment (Kerr et al, 2006). In terms of cycling, Rogerson et al (2016) compared a range of psychological outcomes of riding stationary bikes in green outdoors and indoors settings including directed attention, mood, perceived exertion, social interaction time, intention for future exercise behaviour and enjoyment.…”
Section: Benefits Of Exposure To Naturementioning
confidence: 99%
“…Therefore, mood is objectiveless whereas emotions are directed at an object and might also change in relation to the object (Ekkekakis, 2012;McCarthy, 2011). In this thesis, the researcher was particularly interested in investigating the emotional responses to different environments and exercise events, since positive emotions have been linked to experiences with nature and adherence and uptake of PA (Plante et al, 2006;Rogerson, Gladwell, Gallagher, & Barton, 2016). However, the POMS was initially developed for use within the clinical population so that this scale mainly assessed negative moods and was a non-sport-specific scale.…”
Section: Sport Emotion Questionnairementioning
confidence: 99%